Deep clinical and neuropathological phenotyping of Pick disease. Issue 2 (25th December 2015) - Irwin, David J.; Brettschneider, Johannes; McMillan, Corey T.; Cooper, Felicia; Olm, Christopher; Arnold, Steven E.; Van Deerlin, Vivianna M.; Seeley, William W.; Miller, Bruce L.; Lee, Edward B.; Lee, Virginia M.‐Y.; Grossman, Murray; et al.
Abstract : Objective: To characterize sequential patterns of regional neuropathology and clinical symptoms in a well‐characterized cohort of 21 patients with autopsy‐confirmed Pick disease. Methods: Detailed neuropathological examination using 70μm and traditional 6μm sections was performed using thioflavin‐S staining and immunohistochemistry for phosphorylated tau, 3R and 4R tau isoforms, ubiquitin, and C‐terminally truncated tau. Patterns of regional tau deposition were correlated with clinical data. In a subset of cases (n = 5), converging evidence was obtained using antemortem neuroimaging measures of gray and white matter integrity. Results: Four sequential patterns of pathological tau deposition were identified starting in frontotemporal limbic/paralimbic and neocortical regions (phase I). Sequential involvement was seen in subcortical structures, including basal ganglia, locus coeruleus, and raphe nuclei (phase II), followed by primary motor cortex and precerebellar nuclei (phase III) and finally visual cortex in the most severe (phase IV) cases. Behavioral variant frontotemporal dementia was the predominant clinical phenotype (18 of 21), but all patients eventually developed a social comportment disorder. Pathological tau phases reflected the evolution of clinical symptoms and degeneration on serial antemortem neuroimaging, directly correlated with disease duration and inversely correlated with brain weight at autopsy. The majority of neuronal and glial tau inclusions were 3R tau–positive and 4R tau–negative in sporadic cases. There was a relative abundance of mature tau pathology markers in frontotemporal limbic/paralimbic regions compared to neocortical regions. Interpretation: Pick disease tau neuropathology may originate in limbic/paralimbic cortices. The patterns of tau pathology observed here provide novel insights into the natural history and biology of tau‐mediated neurodegeneration. Ann Neurol 2016;79:272–287